RANCANG BANGUN APLIKASI AKADEMIK BERBASIS WEBSITE PADA RUMAH GEMILANG INDONESIA DEPOK - Muhidin, Muhidin; Mulyana, Nana; Ali, Toni Saidun; Firmansyah , Hadi; Basamekha, Shuhd Khaled Hood; Santoso, Imam (Yayasan Bina Internusa Mabarindo, 2024)
Rumah Gemilang Indonesia is an empowerment program unit and training center under the Al-Azhar National Amil Zakat Institute Program directorate. The current collection of academic data is felt to be less effective because it is still done manually. One of the superior features planned is an online report card system that allows academic staff and students to access the academic data needed for their respective needs. The method of collecting data in the preparation of this thesis is the method of observation, interviews and literature study. A web development method developed using the Code Igniter framework whose programming language is PHP based, Code Igniter applies the MVC (Model, View, Controller) concept which makes it easier for developers to design a website. By developing this academic application, it can make it easier for academic staff to manage academic data and student report card scores online, which will be very effective and efficient in terms of time and students can immediately see the results of their report card scores online by accessing This academic application is through a website that is opened using a browser.